Is it Possible for Extended Confiscation to Become an Effective Legal Tool for the Lithuanian Law Enforcement Authorities and Courts? - Gutauskas, Aurelijus (Teisė, 2024)
The article deals with some problematic aspects of the extended confiscation of property in Lithuania after the decision of the Constitutional Court of the Republic of Lithuania of 12 October 2023 on the compliance of this Criminal Law institute with the Constitution of the Republic of Lithuania. A question arises whether the extended confiscation of property works only if there is sufficient reason to believe that the property has been obtained by means of a criminal offence, in the absence of mandatory conditions for such confiscation laid down in the Criminal Law, in accordance with the principles of criminal procedure, and whether it does not contravene Articles 23 (right to property and its inviolability) and 31 (presumption of innocence) of the Constitution of the Republic of Lithuania. The author raises the rhetorical question of the effectiveness of extended confiscation in law enforcement and judicial practice. Based on the Case Law of the Supreme Court of Lithuania and the European Court of Human Rights, the aim is to assess the peculiarities of the legal regulation of extended confiscation of property and its practical application. It attempts to clarify the content of the concept of acquisition of property by criminal means as defined in the Criminal Law, and to answer the question whether extended confiscation of property should be considered a punishment or a preventive measure.